Constructibility and mathematical existence - Chihara, Charles S., 1932- (Clarendon Press ; Oxford Univ. Press, 1990)
Concerned with the problem of existence in mathematics, this volume develops a mathematical system in which there are no existence assertions but only assertions of constructibility. It explores the philosophical implications of such an approach in the writings of Field, Burgess, Maddy and Kitcher.